2016
DOI: 10.1364/oe.24.00a832
|View full text |Cite
|
Sign up to set email alerts
|

Omnidirectional, polarization-independent, ultra-broadband metamaterial perfect absorber using field-penetration and reflected-wave-cancellation

Abstract: In this work, we present the result of nickel (Ni)-based metamaterial perfect absorbers (MPA) with ultra-broadband close-to-one absorbance. The experimental broadband characteristic is significantly improved over the past effort on metamaterial perfect absorbers. An in-depth physical picture and quantitative analysis is presented to reveal the physical origin of its ultrabroadband nature. The key constituent is the cancellation of the reflected wave using ultra-thin, moderate-extinction metallic films. The ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…In a recent study, it was theoretically and experimentally demonstrated that the use of planar unpatterned metal-insulator (MI) pairs can provide an ultra-broadband light absorption where the absorption bandwidth can extend to longer wavelengths by adding up the number of pairs. 40 After the study, a wide variety of MI combinations including W-Al 2 O 3 , 41 Cr-SiO 2 , 42 Ag-Si, 43 and Ni-SiO 2 44 were later utilized to improve the absorption capability of this architecture. A substantial enhancement in the light absorption capacity of these MI multilayer designs was achieved by the introduction of tapered configuration.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, it was theoretically and experimentally demonstrated that the use of planar unpatterned metal-insulator (MI) pairs can provide an ultra-broadband light absorption where the absorption bandwidth can extend to longer wavelengths by adding up the number of pairs. 40 After the study, a wide variety of MI combinations including W-Al 2 O 3 , 41 Cr-SiO 2 , 42 Ag-Si, 43 and Ni-SiO 2 44 were later utilized to improve the absorption capability of this architecture. A substantial enhancement in the light absorption capacity of these MI multilayer designs was achieved by the introduction of tapered configuration.…”
Section: Introductionmentioning
confidence: 99%
“…However, these modifications do not adequately improve the absorption upper edge. Even using a larger number of [MI] N pairs (e.g., 16 pairs) cannot significantly substantiate the BW [32]. In a recent article, our group revealed an extraordinary optical response of bismuth (Bi) metal in lightperfect absorption [46].…”
Section: Lithography-free Multilayer Perfect Absorbersmentioning
confidence: 96%
“…Different metal–insulator combinations were utilized to obtain ultrabroadband light absorption from these multilayer designs. W‐Al 2 O 3 , Cr‐SiO 2 , W‐SiO 2 , Mo‐SiO 2 , Ag‐Si, Bi‐LiF, and Ni‐SiO 2 are some examples of these MI pairs to obtain perfect broadband absorption. Further improvements can be also achieved using different strategies; excitation of multiple modes in a multithickness absorbing layer, reducing the effective permittivity of metals via their composition with air, the optimal selection of materials to maximize absorption BW are some examples of these strategies.…”
Section: Light Trapping Schemesmentioning
confidence: 99%